The altered expression levels of miR-186, miR-494 and miR-3651 in OSCC tissue vary from those of the whole blood of OSCC patients - Ries, Jutta; Baran, Christoph; Wehrhan, Falk; Weber, Manuel; Motel, Constantin; Kesting, Marco Rainer; Nkenke, Emeka (Cancer Biomarkers, 2018)
BACKGROUND: Altered expressions of miR-186, miR-494 and miR-3651 in whole blood of OSCC patients have already been demonstrated. However, nothing is known about their expression in tumor tissues. This study aimed at evaluating differences in miRNA expression in OSCC tissues compared to healthy oral mucosa and at checking if the altered expression is reflected in corresponding blood. METHODS: In 53 OSCC and 40 healthy mucosal tissues the expression of miR-186, -494 and -3651 was determined by RT-qPCR and expression levels were compared between the groups. The altered expression in tissues was compared with that determined for corresponding blood. MiR-3651 target genes were identified using TargetScan software. RESULTS: Differential expression of miR-186 and miR-494 could not be observed in tumor tissues compared to normal mucosa (pmiR-186= 0.13; pmiR-494= 0.35). Contrary to the detected upregulation of the miR-3651 in the blood of OSCC patients, a significant downregulation was observed in OSCC tissues. A significant correlation between underexpression and diagnosis was ascertained (p= 0.0001). 1710 possible target genes of miR-3651 were identified. CONCLUSIONS: Decreased expression of miR-3651 in OSCC tissues may be a diagnostic biomarker. The opposite change in expression level in the blood might indicate different functions of this miRNA in circulation and tissue.
EVALuna2:35500